Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I have a wavefunction ($a=1nm$):

$$\psi=Ax\exp\left[\tfrac{-x^2}{2a}\right]$$

for which I already calculated the normalisation factor (in my other topic):

$$A = \sqrt{\frac{2}{a\sqrt{\pi a}}} = 1.06\frac{1}{nm\sqrt{nm}}$$

What I want to know is how to calculate the expectation value for a kinetic energy. I have tried to calculate it analyticaly but i get lost in the integration:

\begin{align} \langle E_k \rangle &= \int\limits_{-\infty}^{\infty} \overline\psi\hat{T}\psi \,dx = \int\limits_{-\infty}^{\infty} Ax \exp \left[{-\tfrac{x^2}{2a}}\right]\left(-\tfrac{\hbar^2}{2m}\tfrac{d^2}{dx^2}Ax \exp \left[{-\tfrac{x^2}{2a}}\right]\right)\,dx =\dots \end{align}

At this point I go and solve the second derivative and will continue after this:

\begin{align} &\phantom{=}\tfrac{d^2}{dx^2}Ax \exp \left[{-\tfrac{x^2}{2a}}\right] = A\tfrac{d^2}{dx^2}x \exp \left[{-\tfrac{x^2}{2a}}\right]= A\tfrac{d}{dx}\left(\exp \left[{-\tfrac{x^2}{2a}}\right]-\tfrac{2x^2}{2a}\exp \left[{-\tfrac{x^2}{2a}}\right]\right)= \\ &=A \left(-\tfrac{2x}{2a}\exp \left[{-\tfrac{x^2}{2a}}\right] - \tfrac{1}{a}\tfrac{d}{dx}x^2\exp \left[{-\tfrac{x^2}{2a}}\right]\right) = \\ &=A \left(-\tfrac{x}{a}\exp \left[{-\tfrac{x^2}{2a}}\right] - \tfrac{2x}{a}\exp \left[{-\tfrac{x^2}{2a}}\right] + \tfrac{x^3}{a^2}\exp \left[{-\tfrac{x^2}{2a}}\right]\right) = \\ &= A \left(-\tfrac{3x}{a}\exp \left[{-\tfrac{x^2}{2a}}\right] + \tfrac{x^3}{a^2}\exp \left[{-\tfrac{x^2}{2a}}\right]\right) \end{align}

Ok so now I can continue the integration:

\begin{align} \dots &= \int\limits_{-\infty}^{\infty} Ax \exp \left[{-\tfrac{x^2}{2a}}\right]\left(-\tfrac{\hbar^2}{2m} A \left(-\tfrac{3x}{a}\exp \left[{-\tfrac{x^2}{2a}}\right] + \tfrac{x^3}{a^2}\exp \left[{-\tfrac{x^2}{2a}}\right]\right)\right)\,dx = \\ &= \int\limits_{-\infty}^{\infty} -\frac{A^2\hbar^2}{2m}x\exp\left[-\tfrac{x^2}{2a}\right] \left(-\tfrac{3x}{a}\exp \left[{-\tfrac{x^2}{2a}}\right] + \tfrac{x^3}{a^2}\exp \left[{-\tfrac{x^2}{2a}}\right]\right) \,dx\\ &= \int\limits_{-\infty}^{\infty} \frac{A^2\hbar^2}{2m}\left(\tfrac{3x^2}{a}\exp \left[{-\tfrac{x^2}{a}}\right] - \tfrac{x^4}{a^2}\exp \left[{-\tfrac{x^2}{a}}\right]\right) \,dx\\ &= \frac{A^2\hbar^2}{2m} \underbrace{\int\limits_{-\infty}^{\infty}\left(\tfrac{3x^2}{a}\exp \left[{-\tfrac{x^2}{a}}\right] - \tfrac{x^4}{a^2}\exp \left[{-\tfrac{x^2}{a}}\right]\right) \,dx}_{\text{How do i solve this?}}=\dots\\ \end{align}

This is the point where I admited to myself that I was lost in an integral and used the WolframAlpha to help myself. Well I got a weird result. My professor somehow got this ($m$ is a mass of an electron) but I don't know how:

\begin{align} \dots = \frac{\hbar^2}{2m}\cdot\frac{3}{2a} = \frac{3\hbar^2}{4ma} = 0.058eV \end{align}

Can anyone help me to understand the last integral? How can I solve it? Is it possible analyticaly (it looks like professor did it, but i am not sure about it)?

share|improve this question
4  
Wolfram/Mathematica definitely can do those integrals, but you missed some signs when entering the input ($e^{x^2/a}$ instead of $e^{-x^2/a}$). If you use Mathematica, it's good advice to teach Mathematica that $a > 0$, i.e. use "$Assumptions = {a>0}" for example. –  Vibert Aug 1 '13 at 23:17
    
Now that i have fixed the input in Wolfram alpha i get a result $9/4\,\sqrt{\pi a}$ while $A^2=2/a\,\sqrt{\pi a}$ and so I still get a different result than my prof: $\dfrac{A^2\hbar^2}{2m}9/4\,\sqrt{\pi a} = \dfrac{2\hbar^2}{a\sqrt{\pi a}2m}9/4\,\sqrt{\pi a} = \frac{9\hbar^2}{4a m}$ –  71GA Aug 1 '13 at 23:56
    
+1 to eliminate the downvote . –  Dimensio1n0 Aug 2 '13 at 9:30

2 Answers 2

up vote 1 down vote accepted

My statistical physics professor call those ones Laplace integrals $I(h)$.

$$I(h)=\int_{0}^{\infty}x^{h}e^{-a^2x^2}dx$$

Note that

$$\int_{-\infty}^{\infty}x^{h}e^{-a^2x^2}dx=2I(h) $$

some values

$$I(0)=\frac{\sqrt{\pi}}{2a}, I(1)=\frac{1}{2a^2}, I(2)=\frac{\sqrt{\pi}}{4a^3},I(3)=\frac{1}{2a^4}, I(4)=\frac{3\sqrt{\pi}}{8a^5} $$

You may brute force by integrating by parts to get rid of $x^{h}$ and use $I(0) $ a classical result, or you may use induction over $h$ or some other method.

share|improve this answer
    
So you think i can solve the integral by per partes? –  71GA Aug 2 '13 at 7:28
    
Yes, you only have to know $I(0)$ and decrease the term $x^{h}$ until you get $I(0)$, and of course symmetries such as the integral of an odd function in a symmetric interval is zero and so on. –  Jorge Aug 2 '13 at 7:52

In your problem, you need integrals of kind :

$I_{2n} = \int x^{2n} e^{- \large \frac{x^2}{a}} ~ dx$

Note first that $I_0 = (\pi)^\frac{1}{2} (\frac{1}{a})^ {-\frac{1}{2}}$

Now, it is easy to see that there is a reccurence relation between the integrals :

$$I_{2n+2} = - \frac{\partial I_{2n}}{\partial (\frac{1}{a}) } $$

For instance, $$I_2 = - \frac{\partial I_{0}}{\partial (\frac{1}{a}) } = \frac{1}{2}(\pi)^\frac{1}{2} (\frac{1}{a})^ {- \large\frac{3}{2}} = \frac{1}{2}(\pi)^\frac{1}{2} ~a^ {\large\frac{3}{2}}$$

$$I_4 = - \frac{\partial I_{2}}{\partial (\frac{1}{a}) } = \frac{3}{2} \frac{1}{2}(\pi)^\frac{1}{2} (\frac{1}{a})^ {- \large\frac{5}{2}} = \frac{3}{2} \frac{1}{2}(\pi)^\frac{1}{2} ~a^ {\large\frac{5}{2}}$$

A general formula is :

$$I_{2n} = I_0 ~(2n-1)!! ~(\frac{a}{2})^n = \frac{(\pi)^\frac{1}{2}}{2^n} ~(2n-1)!! ~a^{n+\frac{1}{2}}$$ where $(2n-1)!! = (2n-1)(2n-3)......5.3.1$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.